Broadband Power Line Communication for Integration of Energy Sensors within a Smart City Ecosystem - Slacik, Jan; Mlynek, Petr; Rusz, Martin; Musil, Petr; Benesl, Lukas; Ptacek, Michal (Sensors (Basel, Switzerland), 2021)
The popularity of the Power Line Communication (PLC) system has decreased due to significant deficiencies in the technology itself, even though new wire installation is not required. In particular, regarding the request for high-speed throughput to fulfill smart-grid requirements, Broadband Power Line (BPLC) can be considered. This paper approaches PLC technology as an object of simulation experimentation in the Broadband Power Line Communication (BPLC) area. Several experimental measurements in a real environment are also given. This paper demonstrates these experimental simulation results as potential mechanisms for creating a complex simulation tool for various PLC technologies focusing on communication with end devices such as sensors and meters. The aim is to demonstrate the potential and limits of BPLC technology for implementation in Smart Grids or Smart Metering applications.
Keywords: line; measurement; simulation; power; broadband; communication; network; adaptive; standard